КЕРДЕР МАДАНИЯТИ МЕТАЛЛСОЗЛИК ҲУНАРМАНДЧИЛИГИ - Турганов, Б.Қ. (SCIENCE and SOCIETY, 2024)
The article examines metalworking craft in the monuments of the Kerder culture on the basis of archaeological materials. In such monuments as Kuyukkala, Khayvankala, Tokkala, the production of iron and copper products was established. The analysis of archaeological materials shows that in the VII-VIII centuries, the production of metalworking products on the monuments of the Kerder culture was progressive.